2011
DOI: 10.1016/j.jaac.2011.09.017
|View full text |Cite|
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Multisystemic Therapy and a Statutory Therapeutic Intervention for Young Offenders

Abstract: The superiority of the MST condition in reducing offending and antisocial behavior suggests that MST adds value to current U.K. statutory evidence-based youth services. The provision of MST does not supplant existing services but is best used to facilitate the appropriate and cost-effective organization of statutory services for young persons and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
151
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(157 citation statements)
references
References 37 publications
4
151
1
1
Order By: Relevance
“…Four of these were rated "strong" (Asscher Butler et al 2011;Sawyer and Borduin 2011;Sundell et al 2008); four others were rated as "good" Letourneau et al 2009;Ogden and Hagen 2006;Weiss et al 2013) and three were rated "weak" (Glisson et al 2010;Henggeler et al 2006;Timmons-Mitchell et al 2006).…”
Section: Quality Of Included Studies In Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Four of these were rated "strong" (Asscher Butler et al 2011;Sawyer and Borduin 2011;Sundell et al 2008); four others were rated as "good" Letourneau et al 2009;Ogden and Hagen 2006;Weiss et al 2013) and three were rated "weak" (Glisson et al 2010;Henggeler et al 2006;Timmons-Mitchell et al 2006).…”
Section: Quality Of Included Studies In Reviewmentioning
confidence: 99%
“…Sample sizes were relatively small with three studies having less than 100 participants Ogden and Hagen 2006;Timmons-Mitchell et al 2006). Few studies specifically reported on having undertaken power calculations (only Butler et al 2011;Glisson et al 2010) making it difficult to assess whether the sample size was adequate to detect a true effect.…”
Section: Quality Of Included Studies In Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This question points to the need for further research in relation to those treatments that appear to be effective in some contexts but not in others. Multisystemic Therapy, for example, can boast of successful trials in the United States and Norway, but failed replication in Sweden and Canada [9][10][11][12][13][14][15][16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…This study is in agreement with [29] who noted that young people with ADHD have high rates of depression, anxiety and conduct disorder. If left untreated ADHD will lead to other psychological problems [33].…”
Section: Discussionmentioning
confidence: 99%